SCUBA Learning Video for Diving Courses - Ayu Rahayu; Arief Nuryadin; Ridwan Afrizal; Amal Maftuh Khoiri (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2021)
SCUBA diving is one of the studies that must be mastered by students taking Diving courses in the UNTIRTA Sports Science Study Program, especially students who will take the Sport Tourism concentration. This research aims to develop SCUBA learning video as an alternative long distance learning media for diving courses in Pandemic Covid-19. Procedure in this research used refers to the 4D model with 4 stages, namely define, design, develop, and disseminate. The instruments used in this research include observation sheet, media expert validation questionnaire, material expert validation questionnaire, small-scale & large-scale trial questionaire. Participants in this research activity were 3 media experts, 3 material experts (diving instructur ADSI, POSSI, & SSI), 9 students for small-scale trials and 26 students for large-scale trials. Students who conduct small-scale and large-scale trials are students of the 2020 class of sports science study program who will take diving course. The data collection techniques in this research were carried out by recapitulating and analyzing the results of the questionnaire from all participants so that the final product was obtained. Based on the results of the assessment of media experts, material experts, the results of small-scale and large-scale trials, SCUBA learning video is in the very worth it (feasible) category in terms of media and material aspects so that it can be an alternative distance learning media for diving courses, especially the subject SCUBA Diving.